Analisis Peran Tiktok Shop dalam Mendorong Ekonomi UMKM di Indonesia - Vera Maria; Raudohtul Janah (Institut Nalanda, 2024)
E-commerce and digital platforms like TikTok Shop have significantly impacted the business model of MSMEs in Indonesia. This article discusses the role of e-commerce in promoting the growth of MSMEs and the local economy through quality products and competitive pricing. TikTok Shop has opened opportunities for MSMEs to market their products creatively through short videos and other features, including collaboration with influencers to expand marketing reach. However, the closure of TikTok Shop also negatively impacted traditional market traders, causing a decrease in income and challenges in competing with online prices. To support MSMEs, the government coordinates and monitors MSME activities, as well as provides digital-based training programs to improve technical skills. The government also records MSMEs through the Cooperative and Micro, Small, and Medium Enterprises Data System (Simdakop). Effective marketing strategies, such as consistency, planning, and the use of social media, are crucial for MSMEs to remain competitive in an increasingly tight market. With the right efforts from the government, MSMEs are expected to take advantage of existing opportunities and contribute significantly to national economic growth.